Impact evaluation of SLM options to achieve land degradation neutrality in Tunisia: consultant monthly report (February 2017). - Diwediga, Badabate (2017)
This report details mainly the author's professional activities performed with the ICARDA Centre in Amman (Jordan) for the period 1 ' 28 February 2017, under the supervision of Mr. Victor Kimathi (IMMAP, Jordan Office), Dr. Quang Bao Le (Systems- and GIS-based Sustainable Land Management ' SLM, at ICARDA Amman), and Mr. Enrico Bonaiuti (Monitoring Evaluation and Learning ' MEL, ICARDA Amman).